Evaluating and improving worldwide implementation of future air navigation systems - Whelan, Conor (Cranfield University, 2001)
Air traffic congestion problems in many areas of the world are well known and have been highly publicised in recent years. This airspace dilemma, which results in delays and other undesirable knock-on effects, is escalating at a phenomenal rate and requires immediate attention. Correspondingly, there is concern about safety standards in some worldwide airspace regions. In addition, it is imperative that the significant projected growth in air transport movements over the next two decades is accommodated. Thus. there is an urgent need to solve the current airspace problems and plan in a responsible manner to meet forecast demand. Solutions to these predicaments have been developed and are encompassed Linder the auspices of the term. 'future air navigation systems'. The systems include technolo-gies and procedures that merge to optimise the potential of airport and airspace resources so that the capacity. flexibility and safety of these resources are maxiinised. while delays and their operating costs are ininimised. Future air navigation systems use automated communications. navigation and surveillance technologies to provide enhanced air traffic management through continuous information on aircraft positions and intention', so that reductions in separation are possible without compromising safety. However. confusion exists rei-, arding vdiat technologies and procedures COIlStitLItC t1leSC futiire air navigation systems. Additionally. their current worldwide integratioil staILIS IS not as advanc d as it should be and. in fact. remains larljwlý' Unknown. Indeed. their successful introduction is far from guaranteed at present. Therefore. tills research addresses these requirements by evaluating and improving implementation of tile systems on a global basis. Ultimately. this thesis provides a comprehensive analysis that discovers what systems are pertinent and whether or \, \-here they have been applied to date, in addition to developino and validatin- a framework strategy for improved introduction of the future air navigation systems around the world.